Peter Halley : since 2000 - Halley, Peter; Melvin, Jo; Musée d'art moderne Saint-Etienne; Maruani & Noirhomme Gallery ([Saint-Priest-en-Jarez, France] : Musée d'Art Moderne Saint-Etienne Métropole, 2014)
"In Peter Halley's paintings colours clash and conjoin to create a dizzying sensation. at times the optical effect created by the Day-Glo's luminosity is so jarring that the paintings almost hurt the eye. He celebrates effects such as the plethora of colour in neon signs, internet surfing, and our image-saturated media world. The three-dimensional quality of Halley's work asserts the object status of the paintings in a way that photographic reproduction simply cannot represent."--Page 7.
"In collaboration with Maruani & Noirhomme Gallery."
Catalog of an exhibition held at Musée d'Art Moderne Saint-Etienne Métropole, Jan. 18-May 18, 2014.
Essay in English and French.
boek
Keywords: Halley, Peter